Unusual multisystem tuberculosis in a patient with immunosuppression due to HIV: a case report - Aguilar-Villlanueva, Giamfranco (2022)
Tuberculosis is an infectious disease widely spread around the world and is the leading cause of death among people living with human immunodeficiency virus (HIV). Multisystem tuberculosis occurs more frequently in patients with HIV coinfection, and its clinical presentation may be related to the patient’s immunosuppression level. We report the case of a 19-year-old male patient with immunosuppression due to HIV with unusual multisystem tuberculosis affecting the respiratory, digestive and urinary systems. Treatment and etiological factors are described and discussed, and the importance of a prompt multidisciplinary diagnosis and management is highlighted.